Genome skimming provides evidence to accept two new genera (Apiaceae) separated from the Peucedanum s.l. - Song, Bo-Ni; Liu, Chang-Kun; Deng, Jiao-Jiao; Tan, Wei-Yan; Zhou, Song-Dong; He, Xing-Jin (Frontiers in Plant Science, 2025)
BackgroundThe Peucedanum s.l. genus, the backbone member of subfamily Apioideae, includes many medically and economically important plants. Although previous studies have proved that the genus was not a natural taxonomic unit and taxonomists also conducted several taxonomic revisions for taxa of this genus, classifications of numerous taxa of the genus still have not been satisfactorily resolved, especially for those endemic to China. Therefore, we conducted a comprehensive taxonomic revision of taxa within the polyphyletic Peucedanum s.l. genus in this study.MethodsWe used two molecular datasets (103 plastomes and 43 nrDNA sequences) generated by genome skimming to reconstructed a reliable phylogenetic framework with high support and resolution. In addition, we also investigated the divergence time of core clade of endemic taxa.Results and DiscussionBoth analyses failed to recover Peucedanum s.l. as a monophyletic group and robustly supported that P. morisonii, the representative of Peucedanum s.s., was distantly related to other Peucedanum s.l. members, which implied that these Peucedanum s.l. taxa were not “truly Peucedanum plants”. Among these Peucedanum s.l. members, plastid-based phylogenies recognized two monophyletic clades, clade A (four species) and clade B (10 taxa). Meanwhile, obvious recognized features for morphology, plastome, and chromosome number for each clade were detected: dorsally compressed and glabrous mericarps with filiform dorsal ribs, winged lateral ribs, numerous vittae in commissure and each furrow, IRa/LSC border falling into rpl23 gene, an overall plastome size of 152,288-154,686 bp, and chromosome numbers of 2n=20 were found in clade A; whereas dorsally compressed and pubescent mericarps with filiform dorsal ribs, winged lateral ribs, numerous vittae in commissure and each furrow, IRa/LSC border falling into the ycf2 gene, an overall plastome size of 146,718-147,592 bp, and chromosome numbers of 2n=22 were discovered in clade B. Therefore, we established two new genera (Shanopeucedanum gen. nov. and Sinopeucedanum gen. nov.) to respectively accommodate the taxa of clades A and B. Furthermore, molecular dating analysis showed that the diversification of clades A and B occurred in the early Pleistocene and late Pliocene, respectively, which may have been driven by the complex geological and climate shifts of these periods. In summary, our study impelled a revision of Peucedanum s.l. members and improved the taxonomic system of the Apiaceae family.